2012
DOI: 10.1109/tcsi.2012.2188956
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical System Guided Mapping of Quantitative Neuronal Models Onto Neuromorphic Hardware

Abstract: We present an approach to map neuronal models onto neuromorphic hardware using mathematical insights from dynamical system theory. Quantitatively accurate mappings are important for neuromorphic systems to both leverage and extend existing theoretical and numerical cortical modeling results. In the present study, we first calibrate the on-chip bias generators on our custom hardware. Then, taking advantage of the hardware's high-throughput spike communication, we rapidly estimate key mapping parameters with a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 39 publications
1
21
0
Order By: Relevance
“…In addition to reversing its effect when the membrane potential crosses the reversal potential, our superposable synapse circuit captures a synaptic population's dynamic behavior through its programmable rise time, decay constant, and saturation value. We proved analytically that the QIF neuron's f (g syn ) curve is nonmonotonic-unlike its f (i) curve [9], [13]-and confirmed that silicon neurons driven by our new silicon synapse displayed this behavior. Finally, we demonstrated that the silicon synapse synchronizes silicon neurons most robustly when it is shunting, confirming that reversal potentials can have important implications at the network-level.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…In addition to reversing its effect when the membrane potential crosses the reversal potential, our superposable synapse circuit captures a synaptic population's dynamic behavior through its programmable rise time, decay constant, and saturation value. We proved analytically that the QIF neuron's f (g syn ) curve is nonmonotonic-unlike its f (i) curve [9], [13]-and confirmed that silicon neurons driven by our new silicon synapse displayed this behavior. Finally, we demonstrated that the silicon synapse synchronizes silicon neurons most robustly when it is shunting, confirming that reversal potentials can have important implications at the network-level.…”
Section: Discussionsupporting
confidence: 69%
“…This approach resulted in a heterogenous implementation of the model whose median parameter values matched the specified values but whose variance was determined by device mismatch [13]. For instance, all neurons received a lognormally distributed tonic current with median i in = 0.6 and CV = 22.5% (standard deviation/mean) [13]. This degree of heterogeneity is significantly higher than the previous study's, whose tonic current was normally distributed with CV = 10% [12].…”
Section: Synchronymentioning
confidence: 93%
See 2 more Smart Citations
“…weighted connections). Our analog computational units are spiking silicon neurons [5]; our digital communication fabric is a packet-switched …”
mentioning
confidence: 99%